Waiting time for radiotherapy in women with cervical cancer - do Nascimento, Maria Isabel (Rev Saude Publica, 2016)
OBJECTIVE: To describe the waiting time for radiotherapy for patients with cervical cancer. METHODS: This descriptive study was conducted with 342 cervical cancer cases that were referred to primary radiotherapy, in the Baixada Fluminense region, RJ, Southeastern Brazil, from October 1995 to August 2010. The waiting time was calculated using the recommended 60-day deadline as a parameter to obtaining the first cancer treatment and considering the date at which the diagnosis was confirmed, the date of first oncological consultation and date when the radiotherapy began. Median and proportional comparisons were made using the Kruskal Wallis and Chi-square tests. RESULTS: Most of the women (72.2%) began their radiotherapy within 60 days from the diagnostic confirmation date. The median of this total waiting time was 41 days. This median worsened over the time period, going from 11 days (1995-1996) to 64 days (2009-2010). The median interval between the diagnostic confirmation and the first oncological consultation was 33 days, and between the first oncological consultation and the first radiotherapy session was four days. The median waiting time differed significantly (p = 0.003) according to different stages of the tumor, reaching 56 days, 35 days and 30 days for women whose cancers were classified up to IIA; from IIB to IIIB, and IVA-IVB, respectively. CONCLUSIONS: Despite most of the women having had access to radiotherapy within the recommended 60 days, the implementation of procedures to define the stage of the tumor and to reestablish clinical conditions took a large part of this time, showing that at least one of these intervals needs to be improved. Even though the waiting times were ideal for all patients, the most advanced cases were quickly treated, which suggests that access to radiotherapy by women with cervical cancer has been reached with equity.